Evaluation of Optimum Content of Rice Husk Ash to Improve the Hot Asphalt Concrete Performance - Shafabakhsh, Gholamali; Divandari, Hassan; Reza Sajadi, Seyed (International Journal of Engineering and Technology, 2018)
Durability of asphalt pavements is related to choosing proper materials. Fillers as the smallest particles of stone materials, and one of the most important parts of asphalt mixtures, exert pivotal effects on the performance of asphalt mixtures, by filling empty spaces and because of their softness, surface features and chemical compounds. Rice husk ash is one of the waste products of burning rice husk in powerhouses that is accounted as biomass. Recently, a good many of investigations have shown that rice husk ash, as a high quality pozzolan, can be properly replaced of common aggregates. In this study rice husk ash was used as filler in hot mix asphalt, and the result mixturesâ€™ mechanical properties was compared with ordinary mixtures whose filler was stone powder. Asphalt mixture samples with two different aggregate graded, and 0, 25, 50, 75 and 100 percent of rice husk ash which were the substitution of stone powder content, were made and the effects of using rice husk ash on the moisture sensitivity, resilience modulus, rutting and dynamic creep of asphalt mixtures were investigated. The results demonstrated that increase of using rice husk ash as the replacement of prevalent fillers in hot mix asphalts, noticeably improves their performance; however, because of excessive stiffness created by rice husk ash, it's better to use it in optimized percentage. Accordingly, statistical analysis of the testsâ€™ results leads to presenting an optimized model for the content of Rice Husk Ash to be used in hot mix asphalt. Finally, Rice Husk Ash content were suggested 26% for graded number 4 and 48% for graded number 5 as replacements for stone powder filler.Â